2011
DOI: 10.1039/c1dt10265f
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical RPNPR′ pincer ligands and their group 10 complexes

Abstract: Two new unsymmetrical (R)PNP(R')-type pincer ligands based on a bis(tolyl)amine framework have been synthesized and characterized by a variety of techniques, including X-ray crystallography. These ligands have been coordinated to Ni, Pd, and Pt precursors to provide a number of well-characterized group 10 halides. Conversion of these metal halides to metal hydrides was accomplished using borohydride reagents, or by direct interaction of the ligand with the zerovalent metal precursor. The insertion of oxygen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…Nonetheless, we were encouraged by the results because the PNP framework offers facile opportunities for optimization of the ligand via substituent variation. We selected previously reported PNP ligands 15-H , 50 16-H , 60 and 17-H 50 , 61 for further testing in DHBTA. The syntheses of the corresponding Ir-COE complexes are depicted in Scheme 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we were encouraged by the results because the PNP framework offers facile opportunities for optimization of the ligand via substituent variation. We selected previously reported PNP ligands 15-H , 50 16-H , 60 and 17-H 50 , 61 for further testing in DHBTA. The syntheses of the corresponding Ir-COE complexes are depicted in Scheme 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Kemp, Goldberg, et al also reported that Pd hydrides supported by unsymmetrical Ph 2 PNP R 2 ligands (33 a/b,(2-Ph 2 P(4-methyl-phenyl))(2-R 2 P(4-methylphenyl))amido, Figure 4) can undergo O 2 insertion to form PdÀOOH and PdÀOH moieties. [65] Studies of O 2 insertion into Pd II ÀH bonds in non-pincerligated systems by Stahl et al revealed a different mechanism. [66][67][68][69] In this case, initial reductive elimination of HX from the Pd II hydride complex to generate a Pd 0 species (Scheme 8) is followed by reaction of the Pd 0 with O 2 to form an h 2 -peroxo complex (as described above).…”
Section: Formal Insertion Of O 2 Into Pd II àH Bondsmentioning
confidence: 99%
“…Unsymmetrical PNP ligands that support PdÀH complexes demonstrating O 2 reactivity. [65] Scheme 8. Formal oxygen insertion into a PdÀH bond by a mechanism involving reductive elimination.…”
Section: Insertion Of O 2 Into Pd II àR Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The majority of these compounds have been obtained in direct one-pot reactions in solution; and a few other approaches, such as post-synthetic modication and mechanochemistry, have been recently reported. 11,12 Among N,N,N type pincer ligands, those with symmetric 1,3-bis-(arylimino)isoindoline are investigated in catalytical processes due to simplicity of synthesis, ease of deprotonation, robustness, preferential meridional coordination to metal center and stabilization of its certain valence. 10 Another advantage of the pincer ligands is nowadays their asymmetric structure, hemilability and chirality which are the features required for asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%